Comparison of the T2 relaxation time of the temporomandibular joint articular disk between patients with temporomandibular disorders and asymptomatic volunteers - N. Kakimoto (2018)
BACKGROUND AND PURPOSE: T2 relaxation time is a quantitative MR imaging parameter used to detect degenerated cartilage in the knee and lumbar intervertebral disks. We measured the T2 relaxation time of the articular disk of the temporomandibular joint in patients with temporomandibular disorders and asymptomatic volunteers to demonstrate an association between T2 relaxation time and temporomandibular disorder MR imaging findings. MATERIALS AND METHODS: One hundred forty-four patients with temporomandibular disorders and 17 volunteers were enrolled in this study. An 8-echo spin-echo sequence for measuring the T2 relaxation times was performed in the closed mouth position, and the T2 relaxation time of the entire articular disk was measured. Patients were classified according to the articular disk location and function, articular disk configuration, presence of joint effusion, osteoarthritis, and bone marrow abnormalities. RESULTS: The T2 relaxation time of the entire articular disk was 29.3 ± 3.8 ms in the volunteer group and 30.7 ± 5.1 ms in the patient group (P = .177). When subgroups were analyzed, however, the T2 relaxation times of the entire articular disk in the anterior disk displacement without reduction group, the marked or extensive joint effusion group, the osteoarthritis-positive group, and the bone marrow abnormality-positive group were significantly longer than those in the volunteer group (P < .05). CONCLUSIONS: The T2 relaxation times of the articular disk of the temporomandibular joint in patients with progressive temporomandibular disorders were longer than those of healthy volunteers.